The Role Of Digital Technologies In Modern Society And Education Today - pcadmin, Khahhorova Maftuna Baxtiyorovna (Genius Journals, 2025)
Today, digital technologies have become an integral part of both society and education. Their role continues to grow, transforming traditional approaches to learning and social interaction. In education, digital tools enable more interactive and personalized learning experiences, while in society they facilitate communication, access to information, and the development of innovative solutions to complex problems
Keywords: education; society; technology